2014
DOI: 10.1130/g34986.1
|View full text |Cite
|
Sign up to set email alerts
|

Did Late Miocene (Messinian) gypsum precipitate from evaporated marine brines? Insights from the Piedmont Basin (Italy)

Abstract: During the fi rst stage of the Late Miocene Messinian salinity crisis (5.97-5.60 Ma), deposition of sulfates (the Primary Lower Gypsum) occurred in shallow silled peripheral subbasins of the Mediterranean undergoing restricted water exchange with the Atlantic Ocean. Fluid inclusions in Messinian selenite crystals from the Piedmont Basin (northwest Italy) have surprisingly low salinities (average of 1.6 wt% NaCl equivalent), suggesting that parent waters were depleted in Na+ and Cl- compared to modern seawater.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 23 publications
6
56
0
Order By: Relevance
“…This record confirms that the Sorbas Basin and western Mediterranean must have remained connected during deposition of both the Upper Abad marls and the MSC Stage 1 PLE, because the influence of the lower western Mediterranean 87 Sr/ 86 Sr end‐member persisted within the Sorbas Basin. Thus, our model results provide a plausible hypothesis to explain the observations of Natalicchio et al [] and Evans et al []: a positive freshwater budget over part of the precessional cycles may have led to incorporation of meteoric water within the gypsum.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This record confirms that the Sorbas Basin and western Mediterranean must have remained connected during deposition of both the Upper Abad marls and the MSC Stage 1 PLE, because the influence of the lower western Mediterranean 87 Sr/ 86 Sr end‐member persisted within the Sorbas Basin. Thus, our model results provide a plausible hypothesis to explain the observations of Natalicchio et al [] and Evans et al []: a positive freshwater budget over part of the precessional cycles may have led to incorporation of meteoric water within the gypsum.…”
Section: Discussionsupporting
confidence: 75%
“…Although the cycles studied here were deposited ~580 kyr before the onset of the MSC and deposition of Primary Lower Evaporites (PLE), the inference that the Sorbas Basin had a positive hydrologic budget is consistent with inferences for PLE at two locations including Sorbas. Natalicchio et al [] found that the salinity of inclusions in gypsum from the Piedmont Basin (northwest Italy) is very low. In contrast, gypsum from the Conti Vecchi solar salt works (Sardinia, Italy), where seawater is evaporated to concentrate gypsum and halite as commercial products, has inclusions with high salinity, matching that of the precipitating brine.…”
Section: Discussionmentioning
confidence: 99%
“…The Messinian succession is particularly well-exposed on the Torino Hill-side area as well as in the Langhe domain, which are situated in the northern and southern parts of the Tertiary Piedmont Basin, respectively. It has been thoroughly studied over the last few years and turned out to be particularly helpful in the interpretation of the events related to the MSC in the marginal basins of the peri-Mediterranean area (Dela Pierre et al, 2007Pierre et al, , 2012Natalicchio et al, 2014). The Messinian succession of the Tertiary Piedmont Basin (TPB) has been correlated in detail with the main events of the Messinian Salinity Crisis (Dela Pierre et al, 2007.…”
Section: Geology and Stratigraphymentioning
confidence: 99%
“…diatoms ( Fig. 2C; Natalicchio et al, 2014), and loosely packed, fluorescent clay-rich aggregates as much as 500 mm across and locally containing altered diatom frustules. Similar aggregates have been reported from the shale layers interbedded with the gypsum and have been interpreted to represent marine snow floccules that originated by aggregation of clay and diatoms in the overlying water column during episodes of eutrophication and phytoplankton bloom (Dela .…”
Section: Gypsum Filamentous Fossilsmentioning
confidence: 99%